The effects of technostress creators towards employee's job satisfaction in Pejabat Pelajaran Daerah Segamat / Nur Syazwani Abdul Shukor - Abdul Shukor, Nur Syazwani (Faculty of Business and Management, 2013)
The study aims to identify the effects of technostress creators towards employee's job satisfaction. A conceptual model is proposed by following the studies of Ragu-Nathan, (2008) and Manideepa Tarafdar, (2008). A survey of 75 respondents was conducted in the Pejabat Pelajaran Daerah Segamat (PPD) officers. In this study, Pearson Correlation was used in order to test the hypotheses assumed and aiso the research question. It is discovered that the technostress creators and also the employee's job satisfaction in performed daily work activities which is technostress creators is the independent variables that are strongly influence or give the effects towards the employee's job satisfaction. The technostress creators which are Techno-Overload, Techno-Insecurity, Techno-Uncertainty, TechnoComplexity and also Techno-Invasion was also found the significant ~n influencing or effected employee's job satisfaction. The theoretical contribution of this study is the elements of technostress creators that are faced by the employee's and give effects the employee's job satisfaction in order to performed their work.